2021
DOI: 10.3390/ani11123593
|View full text |Cite
|
Sign up to set email alerts
|

Bottlenose Dolphin (Tursiops truncatus) Whistle Modulation during a Trawl Bycatch Event in the Adriatic Sea

Abstract: Marine mammal vocal elements have been investigated for decades to assess whether they correlate with stress levels or stress indicators. Due to their acoustic plasticity, the interpretation of dolphins’ acoustic signals of has been studied most extensively. This work describes the acoustic parameters detected in whistle spectral contours, collected using passive acoustic monitoring (PAM), in a bycatch event that involved three Bottlenose dolphins during midwater commercial trawling. The results indicate a tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Each net has high vertical (11-15 m) and horizontal (25-40 m) net openings, and is towed in mid-water at high speed (4-4.5 knots) to target schools of anchovies (Engraulis encrasicolus) and sardines (Sardina pilchardus), which are an important food source for dolphins [43]. The relatively high speed with the associate unpredictable route changes can results in bycatch events [44]. In fact, besides foraging behind the codend, dolphins have been also seen entering the net to feed during towing [43].…”
Section: Discussionmentioning
confidence: 99%
“…Each net has high vertical (11-15 m) and horizontal (25-40 m) net openings, and is towed in mid-water at high speed (4-4.5 knots) to target schools of anchovies (Engraulis encrasicolus) and sardines (Sardina pilchardus), which are an important food source for dolphins [43]. The relatively high speed with the associate unpredictable route changes can results in bycatch events [44]. In fact, besides foraging behind the codend, dolphins have been also seen entering the net to feed during towing [43].…”
Section: Discussionmentioning
confidence: 99%
“…Table S3 ). Overall, dolphins show a great degree of plasticity in their whistle frequency range, which allows them to quickly respond to changes in their acoustic environments 5 , 49 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Dolphin vocalizations recorded in the Kvarnerić region, Croatia, and in the Bay of Kotor, Montenegro, were compared with those recorded in other Mediterranean and extra-Mediterranean areas, to assess possible differences and analogies (La Manna et al, 2017Manna et al, , 2020Luís et al, 2021;Rako-Gospić et al, 2021;La Manna et al, 2022;Akkaya et al, 2023). An additional study focused on bottlenose dolphin vocalizations recorded during interactions with trawlers (Di Nardo et al, 2023), and one study described the sounds produced by three bottlenose dolphins, including a pregnant female, simultaneously caught in midwater trawl gear with fatal consequences (Corrias et al, 2021).…”
Section: Acoustic Communicationmentioning
confidence: 99%
“…De Carlo et al (2012 reported no bycatch events over 158 hauls between 2008 and 2009. In 2014-2015 there was one bycatch event of one bottlenose dolphin across 1,797 monitored hauls (Sala et al, 2016), while in 2016-2017 there was one bycatch event involving the simultaneous capture of three bot-tlenose dolphins across 1,460 monitored hauls (Sala et al, 2018;Corrias et al, 2021). Between 2006 and 2019, 19 bottlenose dolphins were bycaught, ranging between zero and three animals per year, resulting in an estimated bycatch rate of 0.00075 individuals per haul (Bonanomi et al, 2022).…”
Section: Incidental Mortality In Fishing Gear (Bycatch)mentioning
confidence: 99%